The Cost of Migrating to a Culturally Different Location - Oliver Falck; Alfred Lameli; Jens Ruhose (Center for Economic Studies and ifo Institute (CESifo), 2014)
Ever since Sjaastad (1962), researchers have struggled to quantify the psychic cost of migration. We monetize psychic cost as the wage premium for moving to a culturally different location. We combine administrative social security panel data with a proxy for cultural difference based on historical dialect dissimilarity between German counties. Conditional on geographic distance and pre-migration wage profiles, we find that migrants demand a (indexed with respect to local rents) wage premium of about 1 (1.5) percent for overcoming one standard deviation in cultural dissimilarity. The effect is driven by males, more pronounced for geographically short moves, and persistent over time.
Keywords: D51; J61; R23; 330; migration costs; culture; internal migration; psychic cost